Menelusuri Jejak Kuliner Tembayat dalam Serat Centhini - Minardi Minardi; Samidi Samidi; Yulinar Aini Rahmah (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2021)
Abstract This study aims to determine the kinds or variety of food that was in Tembayat listed in Serat Centhini. For administration, said Tembayat is no longer entered in the population, but at least the word Tembayat the show to an area of old are now in the whole territory of the District of Bayat and most Kecamatan Wedi, still belongs to the region of Klaten Regency to the South. In addition, the study also aims to describe the political atmosphere manufacture of fiber or the work of this paper. This study used qualitative methods, including in the research literature. The object of research, reference, and referral-other referral obtained through written sources. Then confirmed by interviews with community leaders, to know the existence of the names of the food at the moment. In explaining the political atmosphere during the manufacture of Serat Centhini, researchers using the Theory of Soft Power by Joseph Nye. The resulting conclusion is that there are around 48 the name of the food that is written in the Serat Centhini. The condition of this culinary rarely heard by the public, the bias is said to have been a rare occurrence in Tembayat. About the political atmosphere, Serat Centhini was written by the candidate Pakubuwana V, while the father that Pakubuwana IV still reigned in the Kraton Kasunanan Surakarta Hadiningrat. Current conditions, Kraton Surakarta besieged by Pura Mangkunegaran, the Palace of the Sultanate Ngayogyakarta and the Netherlands, or better known as Pakepung. Then to raise the prestige or name Kraton Surakarta then this paper to be a form of resistance from Surakarta. Since that time, no paperwork, as complete as that by loading all the potential of the Island of Java, it is often referred to as the Encyclopedia of Java. — Abstrak Kuliner merupakan kekayaan khazanah kebudayaan yang dimiliki Indonesia. Kuliner-kuliner di Indonesia berkembang sejak dahulu sampai sekarang dan menjadi identitas di setiap daerah. Tulisan-tulisan kuno telah mencatat menu-menu kuliner Nusantara, baik di prasasti, serat kuno, lontar maupun relief candi. Namun juga terdapat menu-menu lain yang tidak tercatat dan hanya diturunkan melalui tutur lisan. Serat kuno yang menyebutkan tentang kuliner diantaranya Serat Centhini Jilid III. Serat Centhini Jilid karya putra mahkota yang bergelar Pakubuwono V dari Karaton Kasunanan Surakarta Hadiningrat. Dari sekian banyak kuliner yang disebut dalam Serat Centhini Jilid III, menyebutkan juga aneka macam kuliner dari Tembayat. Dalam penelitian ini, penelitian menggunakan studi kepustakaan dengan metode kualitatif. Sumber utama adalah Serat Centhini Jilid III, sedangkan sumber pendukungnya adalah tulisan-tulisan yang relevan. Terhitung tidak kurang dari 50 menu kuliner Tembayat yang tersaji. Semuanya yang disampaikan hanya mengenai makanan, sedangkan minuman dan jamu tidak disebutkan. Jenis makanan yang disebutkan meliputi sayuran, urapan, tumis dan lauk-pauk. Masih ada makanan yang dapat dilacak keberadaannya, namun ada makanan yang sudah tidak terdengar lagi di Bayat atau mungkin telah dimodifikasi maupun berganti nama. Kata Kunci: Serat Centhini, Kuliner, Tembayat